Hedging Strategies in Research Articles: A Comparative Analysis of Indonesian Male and Female English Students - Ade Windiana Argina; Nur Ijabah (Acitya: Journal of Teaching and Education, 2022)
Hedge is claimed as linguistic of full commitment or precision commonly used in academic writing to give the appropriate uncertainty, proper strength of claimed data, politeness, and precise presentation in providing and presenting literary works i.e. research articles. This study aimed at revealing the tendency and preferences of Indonesian English Students in applying hedging strategies, and frequencies of hedges use, and if there were any differences between males and females in using hedges in research articles. Data corpus was composed of 40 articles written in English by male and female postgraduate students majoring English Education. The output was categorized which was referred to a combined framework proposed by Holmes (1988), Hyland (1998), Hyland and Milton (1997), Vartala (2001), and Crompton (1997) covering 9 types of hedges. The statistical result showed that although Indonesian Male English Students (IEMSs) employed Hedges in their research articles more frequently than Indonesian Female English Students (IEFSs) did, MANOVA proved that there was no significant effect of gender on the use of hedges in research articles written by Indonesian English Students. Nevertheless, ANOVA result confirmed significant main effects of gender on the use of some types of hedge (Adverb of Frequency, Quantifiers, Epistemic Lexical Verbs and Adjective& Adverb Informal).